Digitalization of automotive industry : Use of video services in the after sales market - Rissanen, Mikael (My University, 2023)
The focus of this thesis is to study what is the current level of digitalization in the automotive industry and how digitalization has changed, especially, the after sales side of the automotive industry in Finland. Due to the continuously developing consumer expectations and needs, Original Equipment Manufacturers (OEMs) are pushing new technologies to the industry to gain better customer satisfaction and to increase the performance in the workshops. This thesis has chosen to focus on the use of video in car workshops, as it has been lately one of the biggest digital changes for the after sales side of the automotive industry. The car dealers and workshops are often guided by OEM regulations, so this paper was conducted by interviewing both the car workshop managers and the OEMs regional aftersales managers to better understand the benefits and challenges that digitalization is bringing. This study exploits the qualitative method in order to better understand the reasons behind the challenges and benefits. The aim of this paper is to provide information on the digitalization of the automotive industry and give insights to why it is beneficial to digitalize the service side in the car workshops but also to what challenges is related to digitalization. It is clear that digital tools have arrived in the automotive industry as well. The change to electronic vehicles (EVs) is boosting the digital transformation and dealers should at least be ready for the change and take it as part of their strategy. The digital tools can be dictated by the OEM or developed and adapted in house. Either way, communication is the key to success. Making sure that all employees know why these changes are coming and why new tools and technologies are adapted to work is the first step to a successful digital journey. Also, the communication between OEM and dealer plays a key role as a lot of the digital tools are coming from the OEM. This way the local manager can communicate to his or her team the upcoming change and make sure that all employees have the understanding and capability to use the new technology.

Tämä tutkielma keskittyy selvittämään, mikä on digitalisaation nykyinen taso ja kuinka digitalisaatio on vaikuttanut ja muuttanut autoalan jälkimarkkinointi palveluita Suomessa. Kuluttajien toiveet ja tarpeet kehittyvät jatkuvasti, mistä johtuen autovalmistajat (OEM:t) lanseeraavat alalle uusia teknologioita parantaakseen asiakaskokemusta ja -tyytyväisyyttä, sekä korjaamoiden suoriutumista. Tässä tutkielmassa on päätetty keskittyä videoiden hyödyntämiseen korjaamoissa, sillä se on ollut yksi viime aikojen merkittävimmistä digitaalisista kehitysaskelista autoalalla. OEM:t usein ohjaavat jälleenmyyjien, sekä korjaamoiden toimintaa, joten tätä tutkielmaa varten haastateltiin korjaamopäälliköitä sekä autovalmistajien jälkimarkkinoinnista vastaavia henkilöitä. Tällä tavoin saatiin laajemmin kartoitettua digitalisaation tuomia hyötyjä ja haasteita. Tutkielma on luonteeltaan laadullinen, koska sen tavoitteena on syvällisemmin ymmärtää syitä digitalisaation haasteiden ja etujen taustalla. Tutkielman tavoitteena on valaista digitalisaation nykytilaa autoalalla ja antaa näkemyksiä siitä, miksi jälkimarkkinointi palveluiden, kuten korjaamoiden, digitalisaatio kannattaa, mutta myös siitä mitä haasteita tämä osaltaan tuo. On selvää, että digitaaliset työkalut ovat tänä päivänä käytössä myös autoalalla. Autojen sähköistyminen osaltaan kiihdyttää digitaalista transformaatiota. Jälleenmyyjien tulisi alkaa valmistautua tähän muutokseen ja huomioida se strategiassaan. Digitaalisia työkaluja voidaan kehittää organisaation sisällä tai niiden käyttöä voi sanella myös OEM:t. Olipa kumpi tahansa vaihtoehto kyseessä, kommunikaatio on avain onnistumiseen. On tärkeää varmistaa, että työntekijät ymmärtävät miksi asioita lähdetään muuttamaan ja miksi työkaluja ja teknologioita ollaan ottamassa käyttöön. Jälleenmyyjän ja OEM:n välinen kommunikaatio on myös erittäin tärkeää, sillä usein digitaaliset muutokset tulevat OEM:n sanelemana. Täten myös paikalliset päälliköt pystyvät kommunikoimaan tulevan muutoksen omille tiimiläisilleen ja voivat varmistaa, että heillä on tarvittava osaaminen uuden teknologian käyttämiseen.
Keywords: cars; car dealers; digital technology; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business